2014
DOI: 10.1016/j.elspec.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of gamma-ray spectral profiles of linear alkanes in the positron annihilation process

Abstract: The positron-electron annihilation gamma-ray spectra of linear alkanes C n H 2n+2 (n=1-12) have been studied systematically. A profile quality (PQ) parameter, χ, is introduced to assess the agreement between the obtained theoretical profiles and the experimental measurements in the entire region of energy shift of the spectra. Together with the Doppler shift (∆ε) of the gamma-ray spectra, the two parameters, χ and ∆ε, are able to provide a more comprehensive assessment of the calculated gammaray spectra with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Conversely, the valence MOs have small FWHMs and large contributions. Here, we mention the lowest occupied valence orbitals (LOVO), which have attracted attention in previous PWP studies [25][26][27][28][29]31 because of the agreement with the FWHM of the experimental spectra. FWHMs.…”
Section: B Annihilation In Moleculesmentioning
confidence: 87%
See 1 more Smart Citation
“…Conversely, the valence MOs have small FWHMs and large contributions. Here, we mention the lowest occupied valence orbitals (LOVO), which have attracted attention in previous PWP studies [25][26][27][28][29]31 because of the agreement with the FWHM of the experimental spectra. FWHMs.…”
Section: B Annihilation In Moleculesmentioning
confidence: 87%
“…5,6,[9][10][11][12][13][14][15][16][17] In addition, the annihilation spectra of molecules and noble gas atoms have been analyzed using the plane-wave positron (PWP) method. [18][19][20][21][22][23][24][25][26][27][28][29][30] The PWP method approximates the positronic wavefunction as a plane wave, while the electronic state is determined by a quantum chemical calculation. However, the PWP method severely overestimates a) Author to whom correspondence should be addressed: nakai@waseda.jp.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in (2,2)-difluoropropane molecule, the two fluoride atoms will dominate the annihilation process rather than the carbon atoms in propane. [32] Fig. 3 (Color online) The local molecular attraction potential (LMAP) of (2,2)-difluoropropane.…”
Section: Applications and Discussionmentioning
confidence: 99%
“…[3] Furthermore, the studies have also shown that there are some special valence electrons in atoms and molecules, which are correlated strongly experimental gamma-ray spectra. [32] These electrons, we called positrophilic electrons, [32−34] are usually underneath the outer valence orbital, and called inner valence electrons.…”
Section: Introductionmentioning
confidence: 99%